(untitled) (Bangladesh Medical Journal, 2019)
Vesico-vaginal fistula (VVF) is still a major global health problem.This study was performed to detect the surgical outcome of 100 VVF patients in National Fistula Centre. A descriptive cross sectional study was carried out among 100 VVF patients fulfilling the inclusion criteria admitted in the National Fistula Centre under the department of Obstetrics and Gynaecology during the study period of April, 2017 to September, 2017. During the period, 100 patients presented for surgical repair at a mean age of 28.7 years (SD7.1). Majority of them (49%) had a parity of one and 57% were less than 20 years old at the time of their first pregnancy. About 83% of women developed VVF following prolonged obstructed labour. Most of the fistula (95%) repaired through vaginal route by flap splitting technique and 73% repaired at 1st time. Recovery of most of the patient (75%) was uneventful. Inadequate post-operative care (26.9%) was the major causes of unsuccessful repair. Obstetric fistula is one of the tragedies of third world countries and it would be better solved by providing surgical procedure and easy access of all women to competent obstetrical care, irrespective of their social and economic status during pregnancy and delivery. Bangladesh Med J. 2019 Jan; 48 (1): 39-43